Rancang Bangun Sistem Informasi Manajemen Persuratan Dinas Pendidikan Banyuwangi - Galang Perdana Putra; Nurudin Santoso; Eriq Muh. Adams Jonemaro (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Correspondence procedure is limited to communication phases that can accommodate the use of security and in terms of the authority signing. The management letter that both can qualify incoming mail and outgoing mail with the appropriate flow implementation. Disposition letters or notes in the form of orders, suggestions or responses after letter read by management. The disposition is the written instructions regarding the continuation of the Act of settlement letter. Banyuwangi, East Java education service is a government agency in the field of education. The service has information and large amounts of data. Data is an important one of these letters, divided into two incoming mail and outgoing mail. In the case study, the Departmen Education there are constraints of Banyuwangi suspended incoming mail caused the leadership was not in the Office or on duty outside the city. So incoming mail undergoes a buildup and to reply or outgoing mail delays. In addition other constraints in terms of the search by searching for the letters one by one. With this the author developed a web-based media in order to perform disposition of incoming mail and outgoing mail process. The process of development of the system will be done using the spiral model that generates two types of users, twenty-nine functional and non functional needs one. Testing is done at the level of the unit, validation and compatibility testing with the results the user is 100% valid.